2006
DOI: 10.1007/bf03325905
|View full text |Cite
|
Sign up to set email alerts
|

Origin and chemical partitioning of heavy metals in riverbed sediments

Abstract: In the present investigation, bulk and chemical partitioning of elements in the Shefa-Rud riverbed sediments are studies. Higher concentrations of elemental concentrations have been observed in estuarine zone when compared with riverine sediments (except for Al, Fe, Pb and Mn). Manganese is mobilized under anoxic conditions prevailing in the Caspian Sea. Lithogenous materials are greatly diluted in the estuarine zone by various pollutants present in the Caspian Sea. Organic metallic bonds are not significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…The concentration of Pb was high in the north, south, and west regions, compared with low concentration in the east region and core zone (P \ 0.05). The spatial distribution of the metals, however, indicated that it had been apparently affected by the surrounding agriculture and industry (Mohiuddin et al 2010;Karbassi et al 2006). In the north region of the study area, the concentrations of metals (except for Pb) were high.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of Pb was high in the north, south, and west regions, compared with low concentration in the east region and core zone (P \ 0.05). The spatial distribution of the metals, however, indicated that it had been apparently affected by the surrounding agriculture and industry (Mohiuddin et al 2010;Karbassi et al 2006). In the north region of the study area, the concentrations of metals (except for Pb) were high.…”
Section: Resultsmentioning
confidence: 99%
“…While abundance of calcareous shells in some zones has lead to the dilution of most of the metals, it appears that Pb and Mn are associated with this phase. Later, Karbassi, et al (2006) reported that higher elemental concentrations have been observed in estuarine zone when compared with riverine sediments (except for Al, Fe, Pb and Mn). Saeedi, et al, (2004) reported the potential of reverine suspended particulate matter and bottom sediments in adsorbing dissolved metals like Cd, Mn.…”
Section: Introductionmentioning
confidence: 98%
“…However, concentrations of the other six metals were considerably lower than the average concentrations of the World Sediment background level. Such discrepancies between concentrations of elements in the area of study with those of mean World Sediments are indicative of considerable deviations in geological units [21].…”
Section: Resultsmentioning
confidence: 93%